PENINGKATAN KINERJA SISWA MELALUI PENDEKATAN SAINTIFIK PADA PEMBELAJARAN IPA TERPADU MODEL WEBBED - Effendi, Rusli (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Integrated science teaching. It was held in one Junior High School in Bandung by using a sample of 25 students who were selected by cluster random sampling technique. Student performance reflects This research aimed to improve student performance through a scientific approach in webbed-based their ability in solving specific tasks given by the teacher, and it can be measured by predetermined criteria. To assess student performance, this study used Student Worksheet as its instrument which was rated by rubric grading performance assessment. This study uses a weak experimental design with the design of the one-shot case study. The average performance of students for the first to third meeting were 66.52, 75.32 and 82.68. This data was analyzed using paired t-test and gained significant value of 0.000. Data showed that the highest student performance came from asking question, and the lowestwasfrom experiment planning category.